2018
DOI: 10.3892/ijo.2018.4310
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin triggers the apoptosis of human triple-negative breast cancer MDA-MB-231 cells via the p53/Bax/Bcl-2 signaling pathway

Abstract: Fluoroquinolone antibiotics induce cytotoxicity in various cancer cell lines and may therefore represent a potentially important source of novel anticancer agents. The aim of the present study was to examine the effect of ciprofloxacin on the viability, redox balance, apoptosis, expression of p53, Bax and Bcl-2, cell cycle distribution and DNA fragmentation of triple-negative MDA-MB-231 breast cancer cells. The results of the present study demonstrated that ciprofloxacin decreases cell viability in a dose- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 43 publications
(61 reference statements)
3
57
0
2
Order By: Relevance
“…Tumorigenesis is due to the disruption of the balance between cell proliferation and apoptosis, and apoptosis signal transduction is the key to cell apoptosis. 34 Among them, apoptosis-related proteins such as the caspase 3 protease family 35 , 36 and the anti-apoptotic protein bcl-2 37 , 38 play a key role in apoptosis. By Western blot, 39 , 40 we detected the expression of Cleaved caspase-3 and bcl-2 to verify the apoptosis in tumor cells.…”
Section: Resultsmentioning
confidence: 99%
“…Tumorigenesis is due to the disruption of the balance between cell proliferation and apoptosis, and apoptosis signal transduction is the key to cell apoptosis. 34 Among them, apoptosis-related proteins such as the caspase 3 protease family 35 , 36 and the anti-apoptotic protein bcl-2 37 , 38 play a key role in apoptosis. By Western blot, 39 , 40 we detected the expression of Cleaved caspase-3 and bcl-2 to verify the apoptosis in tumor cells.…”
Section: Resultsmentioning
confidence: 99%
“…To further verify the inhibitory effect of siASF1B on apoptosis, factors associated with apoptosis were investigated. Bax and p53 are pro-apoptotic genes, and Bcl-2 is an anti-apoptotic gene ( 41 , 42 ). Additionally, studies demonstrated that the activity of caspase-3 is strengthened during the process of cell apoptosis ( 43 - 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2 is an integral membrane protein, and it can form homodimers to protect cells from apoptosis. In contrast, Bax is a proapoptotic gene and can cause mitochondria to release cytochrome C. Cytochrome C leads to caspase 3 activation which is an important mitochondrial apoptotic marker [ 62 , 63 ]. We investigated the ROS-calcium crosstalk in the ER, autophagosome, and their influence on apoptosis in the mitochondria.…”
Section: Discussionmentioning
confidence: 99%